Regulatory Problems of the Deposit Insurance Corporation in the Deposit Guarantee Program for Digital Bank Customers: Problematika Regulasi Lembaga Penjamin Simpanan Dalam Program Penjaminan Simpanan Nasabah Bank Digital - Rabah, Aluf Ra'syiah; Antisha Shakeab, Kharista Dewi (Universitas Islam Indonesia, 2023)
LPS, which functions to guarantee bank customer deposits, often faces various challenges, especially with the existence of digital banks. This research discusses two matters. First, what challenges will the digital bank face in relation to the LPS guarantee program. Second, efforts can be made to answer these challenges. This is a type of normative research using a statutory research approach. The research process carried out by the author resulted in an answer that the current LPS program and regulations have not been able to accommodate the legal certainty of deposit guarantees for digital bank customers, including competition in digital bank interest rates exceeding the LPS guarantee interest, regulations that have not fully accommodated the needs of digital banks and the risk of attacks in cybercrime. This legal uncertainty will certainly pose quite a big risk considering that the rapid growth of digital banks is currently not matched by the certainty of obtaining deposit guarantees. Referring to the research results, the author suggests that LPS create deposit guarantee claim regulations that are not only suitable for traditional banks, but also for digital banks. Such as the legality of proof of electronic savings, digital bank compliance in providing interest to customers and other policies that can be made by LPS and OJK as well as forming regulations regarding the use of AI in the banking and financial sector.Keywords: Legal Certainty, LPS Program, and Digital Bank Challenges. AbstrakLembaga Penjamin Simpanan (LPS) yang berfungsi untuk menjamin simpanan nasabah bank kerap menghadapi berbagai tantangan khususnya dengan eksistensi bank digital. Penelitian ini akan membahas mengenai dua hal. Pertama, tantangan apa saja yang akan dihadapi oleh bank digital dalam kaitannya dengan program penjaminan LPS. Kedua, upaya apa yang dapat dilakukan untuk menjawab tantangan tersebut. Penelitian ini merupakan jenis penelitian normatif dengan menggunakan metode pendekatan penelitian perundang-undangan. Proses penelitian yang dilakukan oleh penulis menghasilkan sebuah jawaban bahwa program dan regulasi LPS saat ini belum mampu mengakomodir kepastian hukum penjaminan simpanan bagi nasabah bank digital di antaranya ialah persaingan suku bunga bank digital melebihi bunga penjaminan LPS, regulasi yang belum sepenuhnya mengakomodir kebutuhan bank digital serta resiko serangan kejahatan siber. Ketidakpastian hukum tersebut tentu akan menimbulkan resiko yang cukup besar mengingat pesatnya pertumbuhan bank digital saat ini tidak diimbangi dengan kepastian untuk mendapatkan penjaminan simpanan. Merujuk pada hasil penelitian, penulis menyarankan agar LPS membuat regulasi klaim penjaminan simpanan yang bukan hanya sesuai untuk bank tradisional, melainkan juga untuk bank digital. Seperti legalitas bukti simpanan elektronik, kepatuhan bank digital dalam memberikan bunga terhadap nasabah dan kebijakan lain yang dapat dibuat LPS maupun OJK serta membentuk regulasi terkait penggunaan AI pada sektor perbankan dan keuangan.Kata kunci: Kepastian Hukum, Program LPS, dan Tantangan Bank Digital.